Pelagostrobilidium wilberti n. sp. (Oligotrichea, Choreotrichida): Morphology and Morphogenesis - Kuppers, Gabriela Cristina (2006)
Morphology, infraciliature, morphogenetic features, and some ecological data for Pelagostrobilidium wilberti n. sp. are described. This new species was collected from a temporary pond in Magdalena, Buenos Aires province, Argentina, which was sampled monthly from August 2003 to July 2005. The species was found in autumn and winter. Observations were made in vivo and after staining with protargol. Pelagostrobilidium wilberti n. sp. measures 63–84 × 42–49 μm in vivo and is conical in shape, with a posterior spine-like cytoplasmic process. It possesses 6 somatic kineties, with kinety 2 sinistrally curved and shorter than the others. The oral apparatus is composed of 25–32 external and two internal membranelles. The macronucleus is horseshoe-shaped and located beneath the oral apparatus; two or three spherical micronuclei lie dorsally. There is a posterior contractile vacuole. Morphogenesis is hypo-apokinetal and begins dorsally between the curved kinety 2 and kinety 3. After the discovery of this new species, the diagnosis of the genus Pelagostrobilidium was amended.